The Role of Customer Experience in Mediating the Effects of Digital Financial Literacy and E-Service Quality on Customer Retention in Digital Banking Services - Perkasa, Syahdad; Ramadhana Agueni, R. Ghifari; Rilo Pambudi, Abi; Mariani, Minsani (Journal Research of Social Science, Economics, and Management, 2026)
The rapid expansion of digital banking services has intensified competition in customer retention, particularly among Generation Z and Millennial users who prioritize seamless and personalized digital experiences. This study investigates the role of customer experience in mediating the influence of digital financial literacy and e-service quality on customer retention in Indonesia's digital banking sector. Employing a quantitative explanatory approach with a cross-sectional design, data were collected from 230 active digital banking users through structured online questionnaires. Structural Equation Modeling–Partial Least Squares (SEM-PLS) was applied to analyze the direct and indirect effects among variables. The findings reveal that digital financial literacy and e-service quality do not directly affect customer retention, but both significantly enhance customer experience, which in turn fully mediates their effect on retention. Customer experience emerges as the central determinant of loyalty, emphasizing the importance of cognitive, emotional, and functional interactions with digital banking services. The study confirms that technical quality and digital literacy alone are insufficient to sustain long-term engagement without fostering positive customer experiences. These results extend theoretical understanding through the Expectation-Confirmation Theory and Service-Dominant Logic frameworks, and provide practical implications for digital banking institutions aiming to design experience-centered strategies to enhance retention among tech-savvy customer segments.